The Quality of the Hadith "The Sleep of the Fasting People Is Worship" in the Perspective of 'Ulum al-Hadis - Dina Sakinah Wijaya; Anfal Bahri (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to explain the definition of hadith science, branches of hadith science, and methods of approaching hadith science in Islamic studies. Then the author will examine the hadith about "the sleep of the fasting people is worship" from the perspective of 'ulûm al-hadīṡ. The hadith about "the sleep of fasting people is worship" is interesting to study because this hadith is often used as an excuse to be unproductive when fasting, especially during Ramadan. The research method used in this study is a qualitative method through library research. The results of this study show that 'ulûm al-hadīṡ is the rule for knowing the condition of sanad and matan of a hadith. At the same time, the object of study is to know the validity and absence of a hadith. Hadith research activities have 4 (four) steps, namely takhrīj al-hadith, i'tibār, rāwi personal research (sanad research), and matan hadith research. The analysis of the hadith "the sleep of fasting people is worship" shows that this hadith is a dhaif hadith. Even some scholars mention that this hadith is false and cannot be used as a hujjah.